Analisis Struktur Berpikir Siswa dalam Menyelesaikan Masalah Aljabar Berdasarkan Teori APOS - Sinta Wati; Prahesti Tirta Safitri; Prawidi Wisnu Subroto (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2026)
This study aims to analyze students’ thinking structures in solving algebraic problems based on APOS theory, which consists of action, process, object, and schema stages. This research employed a qualitative approach with a case study method. The subjects were 32 students of class VIII-6 at SMPN 27 Kota Tangerang in the 2026/2027 academic year. Data were collected through algebraic problem-solving tests, semi-structured interviews, and documentation of students’ written work. The data were analyzed through data reduction, data presentation, and conclusion drawing based on the indicators of APOS stages. The findings showed that students’ thinking structures varied according to their ability levels. High-ability students reached the action, process, and object stages because they were able to understand the problem information, determine variables, construct algebraic models, solve problems systematically, and provide appropriate conclusions. Moderate-ability students were generally at the action and process stages because they were able to construct algebraic models and perform calculations, but they had not fully reflected on the results as an integrated conceptual structure. Meanwhile, low-ability students remained at the action stage because they were only able to follow basic procedures without fully understanding the relationships among variables. These findings indicate that most students still need gradual and reflective algebra learning that emphasizes the development of conceptual understanding.